Shifting global Larix distributions: Northern expansion and southern retraction as species respond to changing climate. (22nd November 2018) - Mamet, Steven D.; Brown, Carissa D.; Trant, Andrew J.; Laroque, Colin P.
Abstract: Aim: Recent and rapid warming is reorganizing terrestrial vegetation, creating novel species assemblages, and shifting range limits. Relative to the evergreen species that currently dominate much of the boreal forest landscape, Larix (larch) distributions may be particularly responsive to climatic change due to their deciduous habit, and quick growth and reproduction. Here, we amassed data from 83 studies to describe and explain observed patterns of Larix range shifts under contemporary climate change. Location: Northern hemisphere. Taxon: Species of the genus Larix, deciduous gymnosperms. Methods: With 181 observations of Larix range limit dynamics, we used five distribution parameters (tree line advance, stand infilling, tree line recession, stand thinning, no response) and their determinants (climate, land use change, natural disturbance) to describe and explain observed patterns of Larix range shifts under contemporary climate change. We ran a redundancy analysis on the matrix of five distribution parameters considered with other climatic and nonclimatic parameters as explanatory variables. We also characterized the climatic niche of Larix species (temperature and precipitation) and how the niche has changed during the 20th century. Results: Of 173 sites studied over the full distribution of Larix, 63% experienced Larix population increases, 18% had population decreases, and no response was detected at 19% of sites. Latitudinal Larix tree lines in Siberia and North America appear to be infilling and shifting their distributions northward, whereas Larix recession and thinning was more common in southern regions, suggesting southern populations may be experiencing greater drought stress than their northern counterparts. Climatic niches of most Larix species shifted towards warmer and wetter conditions, with tree line advance/forest infilling in cool/dry climate space, and recession/thinning in warm/dry space. Main conclusions: Northern expansion is underway or seems imminent for boreal Larix species, primarily L. laricina in North America. Retraction in southern regions and disappearance of some mountainous populations may be inevitable due to their narrow ecological niches. Species restricted to mountainous habitats may expand locally, though will likely not contribute to broad scale range expansion. These changes will depend on suitable climate, disturbance, and dispersal mechanisms.